Wikipedia in the Courts: An examination of the citation of Wikipedia in judicial opinions in Uganda. Issue 5 (October 2019) - Rukundo, Solomon
Abstract: Wikipedia has been cited at least fourteen times by courts of record in Uganda. Courts have a constitutional mandate to interpret the laws of the land. The idea that they are basing their interpretations on information from an encyclopaedia that anyone can edit is rightfully alarming. The ease with which Wikipedia can be edited raises questions about the accuracy, impartiality and permanence of the information contained on the website. This article examines the citation of Wikipedia by courts of record in Uganda highlighting the limitations and potential pitfalls of this practice.